Efficacy of rtsa-byugs vs diclofenac gel in relieving knee pain of patients with osteoarthritis of the knee - Dorji Nidup; Somboon Kietinun; Sunyarn Niempoog; Kusuma Sriyakul (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - Rtsa-byugs, a massage oil from Bhutan, is a traditional herbal formula known for its anti-inflammatory properties and used in osteoarthritis treatment. This study investigates the efficacy of rtsa-byugs vs diclofenacgel in relieving knee pain in osteoarthritis patients. Design/methodology/approach - A single-blind, randomized controlled trial was conducted amongst osteoarthritis knee patients at an orthopedic outpatient department of Thammasat University Hospital. Participants were randomly allocated to the rtsa-byugs (N = 31) or the Diclofenac gel (N = 31) group. Primary outcomes were assessed by the knee injury and osteoarthritis outcome scores (KOOS), visual analog scale (VAS) and goniometer at day 0, 1, 3, 7. Findings - 62 participants completed the study. The result of the KOOS scores demonstrated a significant improvement of symptoms at the end of the study in both treatment groups. Improvement of symptoms, pain, daily life living, sport and recreational score and quality of life assessment showed a significant difference from baseline (p < 0.001) within both groups. The quality of life score for the rtsa-byugs group increased significantly on day 3 and 7. The VAS score in both groups decreased with a significant difference from baseline to day 7. The mean value of extension of angle measurement was decreased in day 7, and the mean of flexion score increased in both groups when compared with the baseline. Research limitations/implications - The duration of the study was very limited and included a small sample consisting of men and women. Originality/value - Rtsa-byugs is safe and effective in relieving pain from osteoarthritis of the knee and can be used as an alternative treatment for knee osteoarthritis.